Common species of pelagic copepods (Crustacea: Copepoda) from the Gulf of Nicoya, Costa Rica. Especies comunes de copépodos (C:rustacea: Copepoda) pelágicos del Golfo de Nicoya, Costa Rica. - Morales-Ramírez, .A. & Z.J.A. Vargas (Revista de Biología Tropical, 1995)
This ís a guide to the common species of pelagic copepods from the Gulf of Nicoya, an estuary on lhe Pacific coast of Costa Rica (lO'N - 85'W). Nine species of calanoids, two of harpacticoids; and one poeeilomastoid were identified from surfaee plankton hauls collected (280 mieron mesh net) June 1991 in the upper GuIf. These twelve species are also cornmon in other tropical. and sub-tropical seas. The species Acartia lilljeborgii Griesbreeht and Paracalanus parvus Claus were the most cornmon. followed by Hemicyclops thalassius Vervoort & Ramirez, Pseudodiaptumus wrigthí Johnson and P. panamensis Walter. Females of the ¡atter species carried eggs.